PERANAN ADMINISTRASI BISNIS DALAM STRATEGI PENGEMBANGAN USAHA - azis, ismi (AGHNIYA: Jurnal Perbankan Syari'ah, 2020)
In the field of business, administration includes carrying out business operations, namely making and implementing major decisions for the organization. Therefore, administration can be defined as a universal process that organizes people and resources efficiently, in such a way as to direct the activities of the organization towards common goals and objectives. The focus of business administration science is to lead the business, in the sense of setting direction and managing organizational processes at a macro level to get optimal results from existing resources. The ability of a business administrator is not only measured by how efficient and effective he leads, but a more basic question.